THE EARLY PALEOZOIC BASITE MAGMATISM IN THE NORTHEASTERN SIBERIAN CRATON - A. I. Kiselev; B. B. Kochnev; V. V. Yarmolyuk; V. I. Rogov; K. N. Egorov (Геодинамика и тектонофизика)
The Early Cambrian tectonomagmatic activation is manifested in the northeastern passive margin of the Siberian Craton within the area of the Olenek uplift, as well as in the Kharaulakh segment of the Verkhoyansk fold‐ thrust belt that was thrusted onto the craton in the Mesozoic. In the Olenek uplift, igneous rocks occur as basite di‐ atremes, small basalt covers, dolerite dykes and sills intruded into the overlying Upper Vendian carbonate sediments. Stratiform bodies of explosive breccias are present in basal sandstones at the bottom of the Lower Cambrian sediment section. According to the zircon‐based U‐Pb datings [Bowring et al., 1993], the age of explosive basite breccias samples from the Olenek uplift (543.9±0.24 Ma) correlates with the age of potash‐rhyolites (534.6±0.5 Ma) from the basal Lower Cambrian conglomerates in the Kharaulakh uplift section. The geodynamic evolution of the northeastern mar‐ gin of the Siberian craton at the end of the Vendian and the beginning of the Cambrian periods is reflected not only in the magmatism, but also in the thicknesses and facial characteristics of the correlating sediments of the regional pas‐ sive sea basins [Pelechaty et al., 1996]. The northern and eastern margins of the craton were subject to progressive uplifting at the end of the Vendian, which resulted in dewatering and paleokarsting. Uplifting was associated with the formation of siliceous clastic shelf sediments in the southern margin of the basin and the explosive and intrusive basite magmatic activations in the Olenek uplift and rhyolite bimodal‐basite magmatic activation in the Kharaulakh uplift. The observed Vendian‐Cambrian stratigraphic relations and manifestations of the basite magmatism suggest that at the northeastern margin of the craton, the lithosphere was subject to stretching. The assumed rift volcanic‐ sedimentary associations are thin and represent the southern, the most remote part of the shoulder of the rift deve‐ loped (in present‐day coordinates) along the northern margin of the Siberian Craton. The chemical specificity of the Lower Cambrian basites and their mantle sources, the bimodal rhyolite‐basalt magmatism, and the Vendian‐Cambrian sedimentation history provide sufficient arguments to consider the Early Paleozoic rifting and the associated magma‐ tic activation as consequences of the plume–lithosphere interaction in the northeastern Siberian Craton. The paleore‐ constructions [Sears, 2012; Khudoley et al., 2013] suggest that the main rifting events occurred due to the lithosphere breakup through the junction zone of the Siberian and North American cratons which existed in the Early Cambrian. It is also assumed that the breakup was accompanied by the formation of a large igneous province which relics are pre‐ sent in the basin complex of the Canadian Cordillera in North America, as well as in the Olenek and Kharaulakh uplifts. The Early Paleozoic rifting and magmatism may reflect the final phase of the disintegration of the Rodinia superconti‐ nent fragments.